Homogeneous Palladium Diselenide pn‐Junction Diodes for Reconfigurable Circuit Applications. (11th February 2022) - Lee, Minjong; Park, Chang Yong; Sim, Sangjun; Lee, Kimoon; Lee, Young Tack
Abstract: Layered 2D materials, owing to their unique physical and electrical properties, have significant potential for use in future nanomaterial‐based electronic devices. Among these, palladium diselenide (PdSe2 ) has recently emerged as a distinct 2D material with air stability and strong ambipolar property. In this study, the versatility of a PdSe2 ‐based split‐gate field‐effect transistor (SG‐FET) using its stable ambipolar nature is demonstrated. By applying sequentially polarized SG biases, the PdSe2 SG‐FET could be operated as a homogeneous and reconfigurable pn‐junction diode. The optimized h‐BN/PdSe2 /h‐BN sandwich SG‐FET exhibits almost symmetric behaviors in the n‐ and p‐channel regions, enabling a reconfigurable single‐inversion AND (SAND) logic gate function, which can be used as a phase difference‐detection circuit composed only of a single component. It is believed that this approach to the reconfigurable diode and its circuit application paves the way for future 2D material‐based electronics. Abstract : Palladium diselenide (PdSe2 ) has attracted significant interest owing to its air stability and strong ambipolar property distinct from other 2D family members. Beyond basic device applications, h‐BN/PdSe2 /h‐BN sandwich split‐gate field‐effect‐transistors are demonstrated to (1) the reconfigurable ideal pn‐junction diode behaviors and (2) the reconfigurable INHIBIT SAND logic gate applications based on strong ambipolar property of PdSe2 .